ECG and echocardiographic findings in 10-15-year-old elite athletes: $hSarah Koch, Michael Cassel, Karsten Linné, Frank Mayer and Jürgen Scharhag - Koch, Sarah; Cassel, Michael; Linné, Karsten; Mayer, Frank; Scharhag, Jürgen (European journal of preventive cardiology, 2014)
Background: Data on electrocardiographic and echocardiographic pre-participation screening findings in paediatric athletes are limited. Methods and results: 10-...